Separation of platinum group metals : photocatalytic reduction and complexation equilibria of Pt(IV), Pd(II) and Rh(III) - Kriek, R. J.(Roelof Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1998.